The prevalence of culture‐confirmed toenail onychomycosis in at‐risk patient populations. (21st November 2014) - Gupta, A.K.; Daigle, D.; Foley, K.A.
Abstract Onychomycosis is a fungal infection of the nail and is the most common nail affliction in the general population. Certain patient populations are at greater risk of infection and the prevalence of onychomycosis reported in the literature has yet to be summarized across these at‐risk groups. We performed a systematic review of the literature and calculated pooled prevalence estimates of onychomycosis in at‐risk patient populations. The prevalence of dermatophyte toenail onychomycosis was as follows: general population 3.22% (3.07, 3.38), children 0.14% (0.11, 0.18), the elderly 10.28% (8.63, 12.18), diabetic patients 8.75% (7.48, 10.21), psoriatic patients 10.22% (8.61, 12.09), HIV positive patients 10.40% (8.02, 13.38), dialysis patients 11.93% (7.11, 19.35) and renal transplant patients 5.17% (1.77, 14.14). Dialysis patients had the highest prevalence of onychomycosis caused by dermatophytes, elderly individuals had the highest prevalence of onychomycosis caused by yeasts (6.07%; 95% CI = 3.58, 10.11) and psoriatic patients had the highest prevalence of onychomycosis caused by non‐dermatophyte moulds (2.49%; 95% CI = 1.74, 3.55). An increased prevalence of onychomycosis in certain patient populations may be attributed to impaired immunity, reduced peripheral circulation and alterations to the nail plate which render these patients more susceptible to infection.